Desain dan Analisis Konstruksi Mesin Potong Specimen Skala Micro Untuk Pengujian Mekanik - Limbong, Ishak S.; Tualaka, Wiwi Efendi; Dwinanto, Matheus M. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
Abstract Specimen cutting is one of the most important and widely used processes in the metal and nonmetal industry. From several existing specimen cutting technologies, mechanical testing in the form of micro cutting was chosen to design and analyze micro-scale specimen cutting machines. Micro cutting specimen is a machine operated in manual or automatic cutting mode, equipped with safety protection function. Design and analysis of micro-scale specimen cutting machines for mechanical testing in the form of micro-cutting using the Solidworks application. There are 3 components analyzed using Solidworks in this study, namely the swing arm, cutting arm and frame components. The results of the stress analysis for the swing arm are 21.797 MPa, the displacement is 2.468 mm and the factor of safety is 2.85. For the cutting arm, the results of the stress analysis are 37,344 MPa, the displacement is 2,296 mm and the factor of safety is 16,613. For the framework, the results of the stress analysis are 2.177 MPa, the results of the displacement analysis are 0.0175 mm and the factor of safety is 12.664. Keywords : Micro Cutting, Solidworks